2014
DOI: 10.1111/jcmm.12293
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐483‐5p/3p cooperate to inhibit mouse liver fibrosis by suppressing the TGF‐β stimulated HSCs in transgenic mice

Abstract: The transition from liver fibrosis to hepatocellular carcinoma (HCC) has been suggested to be a continuous and developmental pathological process. MicroRNAs (miRNAs) are recently discovered molecules that regulate the expression of genes involved in liver disease. Many reports demonstrate that miR-483-5p and miR-483-3p, which originate from miR-483, are up-regulated in HCC, and their oncogenic targets have been identified. However, recent studies have suggested that miR-483-5p/3p is partially down-regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 40 publications
(53 reference statements)
3
46
0
Order By: Relevance
“…29 Recent findings suggest that miR-483-5p directly targets Timp2 ( Figure 6A) in other cells. 30 Using a luciferase assay ( Figures 6B and 6C), we confirmed that miR-483-5p directly targets Timp2 in the ATDC5 cell line. Moreover, the amount of Timp2 protein in ATDC5 cells was downregulated by miR-483-5p mimics and upregulated by inhibitor, and no difference in Timp2 mRNA levels was found among these groups ( Figure 6D).…”
Section: Mir-483-5p Targets Timp2 To Stimulate Cartilage Angiogenesissupporting
confidence: 54%
“…29 Recent findings suggest that miR-483-5p directly targets Timp2 ( Figure 6A) in other cells. 30 Using a luciferase assay ( Figures 6B and 6C), we confirmed that miR-483-5p directly targets Timp2 in the ATDC5 cell line. Moreover, the amount of Timp2 protein in ATDC5 cells was downregulated by miR-483-5p mimics and upregulated by inhibitor, and no difference in Timp2 mRNA levels was found among these groups ( Figure 6D).…”
Section: Mir-483-5p Targets Timp2 To Stimulate Cartilage Angiogenesissupporting
confidence: 54%
“…Importantly, the use of antagomirs provided powerful evidence that these miRs contribute functionally to the therapeutic actions of EVN. The identification of miR-483-5p is of particular interest because, through the targeting of platelet-derived growth factor and tissue inhibitor of metalloprotease-2, miR-483-5p and -3p (non-EV) were shown to cooperatively suppress HSC activation or CCl 4 -induced liver fibrosis [40]. While the miR-34 family was reported to promote liver fibrosis [41], our data suggests a suppressive effect on fibrogenesis and activation in HSC and this is supported by its ability to diminish epithelial to mesenchymal transition in the kidney [42].…”
Section: Discussionmentioning
confidence: 99%
“…Both PDGF-β and TIMP2 are the direct targets of miR-483. Interestingly, overexpression of miR-483 induced carcinogenesis in mouse liver by suppressing cytokine signaling 3 (Socs3) (113).…”
Section: Mir-483mentioning
confidence: 99%